2018
DOI: 10.1177/0044118x18813700
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring in Context: A Comparative Study of Youth Mentoring Programs in the United States and Continental Europe

Abstract: Most of the existing body of research on formal youth mentoring has focused on programs in the United States, with few inquiries into how mentoring programs have taken shape in other contexts. In this article, we compare and contrast programs in the United States and continental Europe to investigate how context shapes the ways in which programs are conceived and implemented. Concerns about inequality and delinquency have been major drivers of program expansion in the United States, while concerns about the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 18 publications
0
31
0
5
Order By: Relevance
“…Culture . Although culture can affect the goals and practices of the relationship [ 156 ], researchers have rarely examined whether the characteristics of the mentoring relationship are universal or culturally dependent [ 157 , 158 ]. Indeed, studies internationally have underscored the widespread notion of mentoring as a warm, caring relationship (see, for example, studies in Hong Kong—Chan and Ho, [ 64 ]: China—Chan et al [ 58 ]; Glasgow—McArthur et al [ 56 , 159 ]; Rwanda—[ 60 ]; UK—[ 107 ]; Sweden—[ 39 ]; and the Czech Republic—[ 160 ], with only passing attention paid to the role played by race and ethnicity in formal mentoring relationships [ 161 , 162 , 163 , 164 , 165 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Culture . Although culture can affect the goals and practices of the relationship [ 156 ], researchers have rarely examined whether the characteristics of the mentoring relationship are universal or culturally dependent [ 157 , 158 ]. Indeed, studies internationally have underscored the widespread notion of mentoring as a warm, caring relationship (see, for example, studies in Hong Kong—Chan and Ho, [ 64 ]: China—Chan et al [ 58 ]; Glasgow—McArthur et al [ 56 , 159 ]; Rwanda—[ 60 ]; UK—[ 107 ]; Sweden—[ 39 ]; and the Czech Republic—[ 160 ], with only passing attention paid to the role played by race and ethnicity in formal mentoring relationships [ 161 , 162 , 163 , 164 , 165 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, a comparison between 66 American mentoring programs and 50 European programs revealed that U.S. programs targeted high-risk populations and marginally focused on mitigation (i.e., prevention and coping with stressful situations), while European programs targeted immigrant and refugee populations and concentrated on inclusion (i.e., concentrating on promotion and positive youth development). The European programs considered mentoring a bidirectional tool for developing intercultural competence [ 157 ]. De Wit et al, [ 166 ] compared Aboriginal and non-Aboriginal mentees in BBBS Canada and reported that Aboriginals were significantly less likely than non-aboriginal adolescents to be in a long-term continuous mentoring relationship.…”
Section: Resultsmentioning
confidence: 99%
“…Inspired by Greek mythology, a mentor is generally a person who possesses certain qualities or is in a position of authority, and who kindly watches over a younger individual so that he or she may benefit from the mentor's support and advice. Mentoring support occurs in different contexts, for example, and without limitations, in supporting disadvantaged youth (Preston et al, 2019), students at risk (Heppen et al, 2018), people entering challenging careers such as nursing (Williams et al, 2018) or teaching (Talbot et al, 2018), or more generally, in any kind of organisation that aims to develop its workforce (Ghosh et al, 2019). In an entrepreneurial context, although other definitions are possible, mentoring is a support relationship between a novice entrepreneur (where lack of experience is key), referred to as a 'mentee', and an experienced business person, referred to as a 'mentor', where the latter helps the former develop as a person.…”
Section: Ese and Mentoringmentioning
confidence: 99%
“…This emotional stability is associated with improvements in academic performance and self-efficiency [ 13 ], as well as a reduction in behavioural problems such as aggression [ 14 ], substance use [ 15 ] or delinquent behaviour [ 16 ]. As a result, mentoring programmes for minors and young people have grown in popularity as an effective intervention strategy for the social inclusion, health and well-being of the most vulnerable collectives [ 17 ]. In the United States, an estimated 2.5 million children and adolescents maintain formal mentoring relationships each year [ 18 ].…”
Section: Mentoring With Vulnerable Adolescentsmentioning
confidence: 99%